Design of simple DC-to-DC wireless power transfer via inductive coupling - Nataraj, Chandrasekharan; Khan, Sheroz; Eniola, Fajingbesi Fawwaz; Selvaperumal, Sathish Kumar (IEEE, 2017)
This research presents a wireless DC-to-DC power transfer over a short distance. Distance of remotely located target from the source coil and received voltage at the load are the major concern in the Wireless Power Transfer (WPT) applications. The inversely proportional behavior of these parameters degrades the system performance. In order to optimize these values and achieving transfer efficiency, microelectronic circuit is developed and simulated using NI Multisim. The transmitter and receiver modules are constructed and their individual blocks are simulated and analyzed for wireless power transfer. Two inductively coupled coils are designed and used in both transmitter and receiver sections. The inverter is designed using H-bridge with five CMOSFET (IRF520NS, IRF5210S) and its gate signal is generated using NE555 timer IC with two output clock signal where one was inverted using an NMOS inverter. Through simulation, it is observed that with such a design, the power transfer has a limited range, and the range will be smaller for smaller receiving coils and improper alignment. A simulated model is proposed and implemented in this paper. The simulation outputs of each unit is plotted and analyzed separately. In addition, transient plot of load resistance versus output voltage are illustrated to analyze the power of dc-dc power transfer circuit. It is observed that the output voltage is increased correspondingly with increasing load resistance and determined good output voltage is harvested with the optimized load resistance is at 1 kΩ and is 4.25 V. Simulated results shows that the proposed system can transfer power with high efficiency. This proposed system could be made commercially viable through further research work.